Information and Communications Technology Challenges as Instructional Media in Gambia Vocational High Schools - Manding Suso; Istanto Wahyu Djatmiko; Muhammad Imron Romadhon; Bubacarr Jobarteh (Faculty of Engineering, Universitas Negeri Yogyakarta, 2021)
This study explores Information and Communications Technology (ICT) challenges for instructional media at five different Vocational High Schools in the Gambia. Three aspects of data were measured: computer knowledge, internet facilities, and instructional media. The method used in this study involved descriptive research. Data collection methods included closed-ended questioners. The population consists of 164 students from grade 10 class, 50 students from Saamasang, 25 students from Bottrop, 25 from John Pickering, 32 students from St. peter’s, and 32 students from Mingdaw. SPSS 22 software was used to manage the gathered data. The data analysis technique was a descriptive and correlation analysis statistic. Correlation analysis serves to find out whether each school has the same challenges of ICT. Findings revealed that computer knowledge, internet facilities, and instructional media pose the highest challenges. This study concluded that the teachers have an excellent chance to improve applied ICT for enhancing quality learning in the Gambia.